1‐Year Results of Combined Modified Wendler Glottoplasty with Voice Therapy in Transgender Women. (30th May 2022) - Rapoport, Sarah K.; Park, Christopher; Varelas, Eleni A; Chang, Joseph; Brown, Sarah K.; Kinberg, Eliezer; Goldberg, Leanne; Courey, Mark S.
Abstract : Background: To date, 1‐year evaluation of pitch elevation in patients undergoing modified Wendler glottoplasty (WG) in combination with VT has not been assessed. Objectives: To determine whether 1‐year pitch elevation is sustained in patients who undergo modified WG in combination with VT for voice feminization. Methods: A retrospective review of patients who underwent WG in combination with voice therapy (VT) was performed from 2016 to 2020. Charts were reviewed for sustained vowel fundamental frequency (F0/a/), speaking fundamental frequency (SF0), and Trans Woman Voice Questionnaire (TWVQ) at preoperative, initial postoperative (3–6 months after surgery), and 12‐month postoperative visits. Results: Change in average F0/a/, SF0 and TWVQ was 50.25 Hz, 32.96 Hz, and 32.6 at 12‐months postoperatively compared to preoperative values. Initial and 12‐month postoperative SF0 were significantly higher than preoperative SF0 (Mann–Whitney U test p  = 0.0042, p  = 0.0010). There was no difference in initial postoperative and 12‐month postoperative SF0 ( p  = 0.50). TWVQ at 12 months was significantly lower than preoperative TWVQ (ANOVA p  < 0.001, Tukey honestly significant difference HSD p  < 0.05). Conclusions: Pitch elevation remains sustained at one year in patients undergoing modified WG in combination with VT. Modified Wendler glottoplasty combined with VT results in relatively long‐term improvements in voice‐related quality of life and is possibly a beneficial addition in the long‐term management of patients who desire voice feminization. Level of Evidence: 4 Laryngoscope, 133:615–620, 2023